2022
DOI: 10.2196/39883
|View full text |Cite
|
Sign up to set email alerts
|

Return-to-Work Following Occupational Rehabilitation for Long COVID: Descriptive Cohort Study

Abstract: Background Emerging evidence suggests that worldwide, between 30% and 50% of those who are infected with COVID-19 experience long COVID (LC) symptoms. These symptoms create challenges with return-to-work (RTW) in a high proportion of individuals with LC. To tailor rehabilitation programs to LC sequelae and help improve RTW outcomes, more research on LC rehabilitation program outcomes is needed. Objective This study describes the characteristics and outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 36 publications
2
34
0
5
Order By: Relevance
“…In our study, the prevalence of most symptoms decreased after rehabilitation, whereas there were persistent physical, psychological, and cognitive dysfunctions. This is in line with the results from Brehon et al [ 88 ], who showed that neuropsychological symptoms improved in healthcare workers after a rehabilitation program. As fatigue is one of the most commonly reported post-COVID symptoms [ 38 ] and the reported prevalence of fatigue at T2 remains high, sustainable treatments and therapies addressing fatigue must be developed and implemented.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, the prevalence of most symptoms decreased after rehabilitation, whereas there were persistent physical, psychological, and cognitive dysfunctions. This is in line with the results from Brehon et al [ 88 ], who showed that neuropsychological symptoms improved in healthcare workers after a rehabilitation program. As fatigue is one of the most commonly reported post-COVID symptoms [ 38 ] and the reported prevalence of fatigue at T2 remains high, sustainable treatments and therapies addressing fatigue must be developed and implemented.…”
Section: Discussionsupporting
confidence: 92%
“…After rehabilitation discharge, 90 out of 124 patients were still unable to work. Brehon et al [ 88 ] confirm this result and indicate that only 53% of workers with post-COVID symptoms returned to work after a rehabilitation program. In our study, many healthcare workers (60 out of 89) were incapacitated for work at baseline.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This result demonstrates the importance of work for well-being. In a recent cohort study, workplace modifications have been found to be the most important factor in supporting the return to work for persons with post-COVID-19 [ 52 ]. Therefore, in the future, focus should be given to how a return to work and stay at work can be supported after COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most commonly reported sequelae are symptoms such as fatigue, dyspnoea, and, in some cases, even a marked deterioration in physical capacity [ 9 , 10 ]. These sequelae affect the quality of life and return to work in the active population [ 11 ]. Thus, it is estimated that the long-term sequelae of COVID-19 in patients after hospital discharge can reach 76% of cases at six months (i.e., at least one symptom at follow-up, such as fatigue, muscle weakness, sleeping difficulties, anxiety, depression, or others), with higher prevalence in women [ 12 ].…”
Section: Introductionmentioning
confidence: 99%